Urban development, power coalitions and citizens participation in Barcelona: a narrative from a critical geography approach - Antònia Casellas (Boletín de la Asociación de Geógrafos Españoles)
From a critical geography approach, the article addresses the debate on the characteristics of governance and urban and economic development strategies in Barcelona. It analyzes the gradual reorientation of local policies, from a management and social redistribution approach that began in the eighties, to a policy dominated by image promotion and capital gains from land development. It identifies the turning point in this process, the characteristics of the agents involved and their decision-making dynamics, addressing the changes in marketing and planning narrative since 2010, from the urban to the metropolitan scale. The article concludes with a statement on the need for more inclusive local governance.